Level of student's satisfaction towards UiTM Bus Service provided by UiTM Kota Kinabalu / Cheesey Marrie ... [et al.] - Marrie, Cheesey; Tausin, Roshasline; Yain, Rozaima; Yain, Salinah; Muhamad, Shema (2014)
People are using transportation in order to move from one point to another point. As students, they also need a good transportation to move in and out from the campus. However, different expectation of students will effect different of level satisfaction towards bus services provided by the campus. The purpose of this research is to study the relevant factors of level satisfaction on Universiti Teknologi MARA Sabah branch bus service and recommendations for this research. The research carried out to focus on the population of NR of UiTM Sabah with different section or place where we only done the research with 150 students by using questionnaires. The findings reveal that only tangibility can explain the level of satisfaction students towards the bus services. In thus, the recommendation the bus service priority is safety and the time promise to increase the students' level of satisfaction.